Kandungan, Resorpsi N dan P serta Specifi c Leaf Area Daun Kakao (Theobroma cacao L.) pada Cekaman Kekeringan - Erma Prihastanti; Soekisman Tjitrosemito; Didy Sopandie; Ibnul Qayim; Christoph Leuschner (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
Plant nutrient absorptions depend on their environment and plants’ stage of development. Beside from soil, nutrient absorption also proceed through resorption in leaves. The resorption efficiency varies based on types of habitat. Drought stress also influences the efficiency of nutrient resorption, growth rate, and plant development. The purpose of this research was to study the change of nitrogen (N) and phosphorus (P) content and leaf resorption value of N and P, and specific leaf area of 6-years old cacao grown under drought stress. Research was carried out in a cacao plantation with 7-years old Gliricidia sepium Jacq. as shading trees. The results showed that drought stress with Troughfall Displacement Experiment (TDE) system did not affect the content and resorption level of N and P of cacao leaves. However, N resorption of cacao leaves tended to increase while P resorption decreased. Cacao plants experienced drought stress have the ability to resorp leaf N for 46.64-50.63%, leaf P for 47.98-58.40%, whereas, the control plants had the leaf N resorption of 45.05-52.97%, and leaf P resorption of 36.64-44.10%. Drought stress for 13 months on 6-years old cacao did not affect specifi c leaf area.